2017
DOI: 10.1108/ijbm-07-2016-0099
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of consumers’ intention to adopt mobile banking services in Zimbabwe

Abstract: Purpose The purpose of this paper is to investigate the determinants of consumers’ intention to adopt mobile banking services in Zimbabwe. Design/methodology/approach A survey of 232 bank customers was conducted in Chinhoyi, Zimbabwe, using a structured questionnaire with Likert-type questions. Customers were randomly intercepted as they walked out of five major banks. Structural equation modelling, independent-samples t-test and one-way ANOVA were used to test research hypotheses. Findings The study found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
117
2
22

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(196 citation statements)
references
References 46 publications
(232 reference statements)
25
117
2
22
Order By: Relevance
“…The last impacting factor among innovation characteristics was perceived risk. This finding was also in line with the previous studies that found the negative impact of it (Laforet & Li, 2005;Makanyeza, 2017;Tan & Teo, 2000). Since this study included only users of mobile banking, perceived risk was not an important barrier to adoption, however, its' effect was significant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The last impacting factor among innovation characteristics was perceived risk. This finding was also in line with the previous studies that found the negative impact of it (Laforet & Li, 2005;Makanyeza, 2017;Tan & Teo, 2000). Since this study included only users of mobile banking, perceived risk was not an important barrier to adoption, however, its' effect was significant.…”
Section: Discussionsupporting
confidence: 91%
“…The innovation adoption generally relies on the analysis of consumer characteristics whose already having purchased the innovation rather than the ones that have not purchased yet; in order to separate adoption intention (Gupta & Arora, 2017;Makanyeza, 2017;Zhou, 2012) and actual behavior (Greer & Murtaza, 2003;Im et al, 2003;Szopiński, 2016).…”
Section: Innovation Characteristics and Innovation Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, those who consider mobile banking useless are not expected to accept it. The study findings confirmed the existing studies that perception of usefulness heightens the adoption of latest technologies [12], [13], [24], [31]. In addition, the findings indicate that mobile banking users think operating mobile banking is effortless and is easy to learn it.…”
Section: Discussionsupporting
confidence: 86%
“…Mobile banking services can be grouped that is transaction-based; which include transferring funds, payments of utility bills, prepaid reload and online shopping while non-transaction based including balance check, transaction history and verification of transaction [13].…”
Section: Zahoor Ur Rehman Siti Sarah Binti Omar Shafie Bin Mohamad mentioning
confidence: 99%